Functional activities of beta-glucans in the prevention or treatment of cervical cancer - Shahla Chaichian; Bahram Moazzami; Fatemeh Sadoughi; Hamed Haddad Kashani; Marsa Zaroudi; Zatollah Asemi (BMC, 2020)
Abstract Cervical cancer is the fourth-ranked cancer in the world and is associated with a large number of deaths annually. Chemotherapy and radiotherapy are known as the common therapeutic approaches in the treatment of cervical cancer, but because of their side effects and toxicity, researchers are trying to discovery alternative therapies. Beta-glucans, a group of glucose polymers that are derived from the cell wall of fungi, bacteria, and etc. it has been showed that beta-glucans have some anti-cancer properties which due to their impacts on adaptive and innate immunity. Along to these impacts, these molecules could be used as drug carriers. In this regard, the application of beta-glucans is a promising therapeutic option for the cancer prevention and treatment especially for cervical cancer. Herein, we have summarized the therapeutic potential of beta-glucans alone or as adjuvant therapy in the treatment of cervical cancer. Moreover, we highlighted beta-glucans as drug carriers for preventive and therapeutic purposes.